Development and validation of a time and motion guide to assess the costs of prevention and control interventions for nosocomial infections: A Delphi method among experts - Tchouaket Nguemeleu E; Boivin S; Robins S; Sia D; Kilpatrick K; Brousseau S; Dubreuil B; Larouche C; Parisien N (Public Library of Science (PLoS), 2020)
Background Nosocomial infections place a heavy burden on patients and healthcare providers and impact health care institutions financially. Reducing nosocomial infections requires an integrated program of prevention and control using key clinical best care practices. No instrument currently exists that measures these practices in terms of personnel time and material costs. Objective To develop and validate an instrument that would measure nosocomial infection control and prevention best care practice costs, including estimates of human and material resources. Methods An evaluation of the literature identified four practices essential for the control of pathogens: hand hygiene, hygiene and sanitation, screening and additional precaution. To reflect time, materials and products used in these practices, our team developed a time and motion guide. Iterations of the guide were assessed in a Delphi technique; content validity was established using the content validity index and reliability was assessed using Kruskall Wallis one-way ANOVA of rank test. Results Two rounds of Delphi review were required; 88% of invited experts completed the assessment. The final version of the guide contains eight dimensions: Identification [83 items]; Personnel [5 items]; Additional Precautions [1 item]; Hand Hygiene [2 items]; Personal Protective Equipment [14 items]; Screening [4 items]; Cleaning and Disinfection of Patient Care Equipment [33 items]; and Hygiene and Sanitation [24 items]. The content validity index obtained for all dimensions was acceptable (> 80%). Experts statistically agreed on six of the eight dimensions. Discussion/Conclusion This study developed and validated a new instrument based on expert opinion, the time and motion guide, for the systematic assessment of costs relating to the human and material resources used in nosocomial infection prevention and control. This guide will prove useful to measure the intensity of the application of prevention and control measures taken before, during and after outbreak periods or during pandemics such as COVID-19.
Keywords: Algorithms; Cross Infection; Delphi Technique; Disinfection; Hand Hygiene; Humans; Infection Control; Mass Screening; Personal Protective Equipment; Sanitation; Time and Motion Studies